Pilot Study of the Gait Deviation Index in Quantifying Overweight Children's Mobility - Liu, Xue-Cheng; Hainsworth, Keri; Simpson, Pippa; Lyon, Roger; Tassone, Channing; Weisman, Steven (Journal of Child Science, 2018)
Childhood obesity in the United States has more than tripled in the past three decades. Differences in lower extremity kinematics between obese and nonobese children during walking have been investigated, but the validity of using the gait deviation index (GDI) for measuring gait in obese children has not been explored. Nine obese children (13.9 ± 2.4 years old) with a body mass index of 33.3 ± 3.5 participated in the study. Reflective markers were placed on all children in a widely used standard lower extremity marker configuration. All participants walked along a 20-foot walkway at a self-selected speed. The kinematic and kinetic measurements for all children were taken, and the GDI for each subject was calculated. The mean ± standard deviation (SD) GDI of the nine obese children was 88.5 ± 12, which was significantly lower than the GDI of the typically developing children (100 ± 10, p < 0.002). There were no statistically significant correlations between the GDI and the Pediatric Quality of Life (PedsQL) Total score or PedsQL Physical Functioning score. Obese children had a significantly increased anterior pelvic tilt, hip flexion, hip adduction, hip adduction moment, knee flexion, knee valgus, and plantar flexion in stance phase (p < 0.05). While in swing phase, obese children had increased hip adduction and knee varus. The kinematic differences may reveal lower limb mal-alignment in obese children during walking. Overall, the GDI can play a major role in evaluating gait pathology in obese children. Future studies will increase the sample size to further evaluate the correlation between the GDI and functional outcomes.
Keywords: gait; gait deviation index; child obesity; mobility